The United Nations Global Compact International Yearbook 2012 - United Nations Global Compact (United Nations, 2013)
The main focus of this latest edition is the 2012 UN Conference on Sustainable Development (Rio+20). The event marked a crossroad for sustainable development and set the sustainability agenda for the next decade. Therefore, the world expected that a strong call for responsible and sustainable business practices – as covered by the United Nations Global Compact – would emerge as a result. The aim of this publication is to provide a global overview of the achievements of the Global Compact. It offers proactive and in-depth information on key sustainability issues to stakeholders all around the world and promotes unique and comprehensive knowledge exchange and learning in the spirit of the Global Compact principles.